Urine stabilization and treatment using lactic acid from fruit and vegetable peels: A potential source of nitrogen fertilizer - Khamala, Tabitha Nekesa (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
This study proposes stabilising urine for use as nitrogen fertilizer in agriculture through lactic acid fermentation (LAF) from fruit and vegetable peel waste. Focused on onsite sanitation, it aims to utilize source-separated urine to enhance food production sustainably. Previous research shows LAF can suppress pathogens in fecal sludge and organic material preservation. The goal is to maximize lactic acid production, retain nitrogen, eradicate odor, and kill bacteria in human urine. Conducted at Meru University of Science and Technology, the research employs a quasi-experimental design. Urine samples from four volunteers will be analyzed for E. coli and nitrogen content before and after treatment. Peels from Gakoromone Market will be washed, air-dried, and stored. LAF will be performed on 300g of peels, fermented anaerobically for 72 hours at 34°C, 37°C, and 40°C, and analyzed with a UV-VIS spectrophotometer. The lactic acid produced will be added to urine samples and stored for seven days. Additionally, a direct fermentation setup will compare direct LAF with lactic acid addition to urine. Physicochemical properties, including temperature, pH, E. coli, and nitrogen content, will be measured using standard methods, such as the Kjeldahl method and MacConkey agar. Statistical analysis will use a Turkey test in one-way ANOVA to identify significant differences. Expected outcomes include higher nitrogen content, lower pH, minimal odor, and reduced E. coli levels in treated urine compared to untreated samples.